PENGARUH EFEKTIVITAS PENERAPAN PERMATA (PENDAFTARAN MANDIRI AKTA TANAH) TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR PERTANAHAN KOTA SEMARANG (STUDI KASUS DI KECAMATAN SEMARANG SELATAN) - Erni Ismawati; Hesti Lestari (Journal of Public Policy and Management Review, 2017)
Public service is an activity that must be done by any government agency as a publik servant. Any effort were made toimprove the quality of service. One of wich in land affairs ministry in Semarang city. Increase claims to ground handling services, make lands service agency in Semarang City, the effort to improve the quality of service. One of which is implement a service that based on web or PERMATA (independent registration of land deed), with the hope can improving quality of service in Land Ofice of Semarang. This study aimed to analyze the influence of the effective application of PERMATA on the quality of services in the Land Office of Semarang. Assessment of each variable is done by PPAT (Land Deed Officer) as the use of PERMATA. This study uses a quantitative method to determine the effectiveness of PERMATA effect on the quality of public services, which involves 27 PPAT in the District of South Semarang. Based on the results of research show that, there is influence between the effectiveness of PERMATA on the quality of public services in the Land Office of Semarang, where the degree of influence that is calculated by the formula shown Kendall Tau Z count> Z table, that is 4.257> 1.96. In addition, test results of the coefficient of determination (KD) shows that the effectiveness of PERMATA effect of 21.3% on the quality of public services in the Land Office of Semarang. Based on these results the researchers concluded, that there is a positive influence between significan and effectiveness of PERMATA Implementation of the quality of public services. The recommendations given by the author that, should be increased maintenance of application, to reduce interference when the application is used, and need for training for officer to improve skill from the officer, when they use modern technologies.